Potential mechanisms underlying the ameliorative effect of Lactobacillus paracasei FZU103 on the lipid metabolism in hyperlipidemic mice fed a high-fat diet. (January 2021) - Lv, Xu-Cong; Chen, Min; Huang, Zi-Rui; Guo, Wei-Ling; Ai, Lian-Zhong; Bai, Wei-Dong; Yu, Xiao-Dan; Liu, Ying-Li; Rao, Ping-Fan; Ni, Li
Graphical abstract: Highlights: L. paracasei FZU103 has the potential to protect against NAFLD associated with hyperlipidemia. The probiotic L. paracasei FZU103 can regulate weight and glycolipid levels in mice. L. paracasei FZU103 alters the intestinal microecological environment of mice fed with HFD. Energy, amino acid, fatty acid and lipid metabolisms play a major role in the preventive effect. The mRNA expression of lipid metabolism were influenced by L. paracasei FZU103 intervention. Abstract: Lactobacillus paracasei FZU103, a probiotic previously isolated from the traditional brewing process of Hongqu rice wine, may have the beneficial effect of improving the disorder of lipid metabolism. This study aimed to determine the beneficial effects of L. paracasei FZU103 on improving hepatic lipid accumulation associated with hyperlipidemia. Results indicated that L. paracasei FZU103 intervention significantly inhibited the abnormal growth of body weight and epididymal white adipose tissue (eWAT), prevented the hypertrophy of epididymal adipocytes, ameliorated the biochemical parameters of serum and liver related to lipid metabolism in HFD-fed mice. Histological analysis also showed that the excessive accumulation of lipid droplets in the livers induced by HFD-feeding was greatly alleviated by L. paracasei FZU103 intervention. In addition, L. paracasei FZU103 also promoted the excretion of bile acids (BAs) through feces. Metagenomic analysis revealed that oral supplementation with L. paracasei FZU103 significantly increased the relative abundance of Ruminococcus, Alistipes, Pseudoflavonifractor and Helicobacter, but decreased the levels of Blautia, Staphylococcos and Tannerella in HFD-fed mice. The relationships between lipid metabolic parameters and intestinal microbial phylotypes were also revealed by correlation heatmap and network. Furthermore, ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTOF/MS)-based liver metabolomics demonstrated that L. paracasei FZU103 had a significant regulatory effect on the metabolic pathways of glycerophospholipid metabolism, fatty acid degradation, fatty acid elongation, unsaturated fatty acids biosynthesis, riboflavin metabolism, glycerolipid metabolism, primary bile acid biosynthesis, arachidonic acid metabolism, etc. Additionally, L. paracasei FZU103 intervention regulated expression of hepatic genes involved in lipid metabolism and bile acid homeostasis, and promoted fecal excretion of intestinal BAs. These findings present new evidence supporting that L. paracasei FZU103 has the potential to improve lipid metabolism, and could be used as a potential functional food for the prevention of hyperlipidemia.